The consequences of upholding deceptive marketing practices and its effect on consumers’ related attitudes including consumer loyalty and consumer trust: Evidence from the fashion industry in the UAE - Noor un Nisa; Angelico Acha; Nazia Dharejo (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This study aims to shed light on how dishonest advertising has harmed the fashion industry in the United Arab Emirates, particularly concerning consumer’s continued patronage and faith in its practices. This study examines how misleading advertising impacts customers’ attitudes and actions, particularly their loyalty and trust in a brand. This research endeavours to examine the data from prior studies and relate them to the residents of the United Arab Emirates. Methodology: Rather than relying on quantitative methods, this study took a qualitative approach, emphasizing interviews and in-depth discussion. Respondents were interrogated in person using the interview technique. The research benefited from applying thematic analysis to comprehend the responses better and examine the answers’ similarities and differences. Participants in this survey are all current U.A.E. residents exposed to fashion industry advertisements regularly. Findings: Three respondent’s insights suggest that they are well aware of the potential impact of deceptive advertising on their customers. Two of the remaining respondents, however, implied ignorance about misleading advertising. They get th at customers need honest product information, significantly when it affects their purchasing decisions. The United Arab Emirates is generally safe because of its stringent laws, such as its consumer protection law, which places a premium on consumer safety. Companies can still make subtle but significant changes to their advertisements without consumers noticing. Implications/Novel Contribution: These results highlight the importance of educating consumers about the perils of manipulative advertising. Consumers should always do their research and never accept anything at face value. As an alternative, they should do their homework to ensure the accuracy of the data they’ll use to make decisions. To provide the most in-depth study based on deceptive marketing, more research into the role of deceptive marketing in the global fashion industry, including the quality of services and the company’s brand image, is needed.